Feasibility, acceptability, and sustainability of Project ECHO to expand capacity for pediatricians in Vietnam - Le Hong Nhung; Vu Duy Kien; Nguyen Phuong Lan; Pham Viet Cuong; Pham Quoc Thanh; Tran Minh Dien (BMC, 2021)
Abstract Background The Project Extension for Community Healthcare Outcomes (ECHO) model is considered a platform for academic medical centers to expand their healthcare workforce capacity to medically underserved populations. It has been known as an effective solution of continuing medical education (CME) for healthcare workers that used a hub-and-spoke model to leverage knowledge from specialists to primary healthcare providers in different regions. In this study, we aim to explore the views of healthcare providers and hospital leaders regarding the feasibility, acceptability, and sustainability of Project ECHO for pediatricians. Methods This qualitative study was conducted at the Vietnam National Children's Hospital and its satellite hospitals from July to December 2020. We conducted 39 in-depth interviews with hospital managers and healthcare providers who participated in online Project ECHO courses. A thematic analysis approach was performed to extract the qualitative data from in-depth interviews. Results Project ECHO shows high feasibility when healthcare providers find motivated to improve their professional knowledge. Besides, they realized the advantages of saving time and money with online training. Although the courses had been covered fully by the Ministry of Health's fund, the participants said they could pay fees or be supported by the hospital's fund. In particular, the expectation of attaining the CME-credited certificates after completing the course also contributes to the sustainability of the program. Project ECHO's online courses should be improved if the session was better monitored with suitable time arrangements. Conclusions Project ECHO model is highly feasible, acceptable, and sustainable as it brings great benefits to the healthcare providers, and is appropriate with the policy theme of continuing medical education of the Ministry of Health. We recommend that further studies should be conducted to assess the impact of the ECHO program, especially for patient and community outcomes.